Anal intraepithelial neoplasia: review and recommendations for screening and management. (November 2013) - Smyczek, Petra; Singh, Ameeta E; Romanowski, Barbara
Anal cancer is a rare malignancy of the distal gastrointestinal tract, often associated with human papillomavirus, the most common sexually transmitted infection worldwide. Currently available screening methods for anal intraepithelial neoplasia, a precursor for anal cancer, combine anal Papanicolaou cytology and high resolution anoscopy with biopsy of suspicious lesions. Significant barriers to establishing anal cancer screening programmes include the small number of healthcare professionals performing high resolution anoscopy and the lack of data showing that anal cancer screening can reduce morbidity and mortality related to anal carcinoma. Despite several controversies surrounding anal cancer screening, the rising incidence of this disease in some groups supports routine screening programmes in high-risk populations, especially in HIV-positive men who have sex with men. This review outlines the epidemiology of anal intraepithelial neoplasia and anal cancer and summarizes issues related to the introduction of anal cancer screening programmes.